Literature review method of mining underground coal gasification - Nguyen, Lê Hồng Sơn; Hoang, An Quốc (Journal of Technical Education Science, 2014)
In my research, I stumbled across something interesting called the underground coal gasification (UCG). This is a process where coal is converted to syngas. The resource for UCG is principally un-mined coal seams. The gasification process creates synthesis gas that can be used as fuel for electricity generation, or feedstock for further chemical processes such as ammonia production or liquid fuels. An oxidant (air, oxygen, or steam) is injected into the coal seam and reacts with the coal and water present in the seam to produce syngas that is extracted through a production well.